2019
DOI: 10.1016/j.jclinepi.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

PubMed coverage varied across specialties and over time: a large-scale study of included studies in Cochrane reviews

Abstract: Objective: PubMed is one of the most commonly used search tools in Biomedical and Life Sciences. Existing studies on database coverage generally conclude that searching PubMed may not be sufficient although some find that the contributions from other databases are modest at best. However, generalizability of the studies of the coverage of PubMed is typically restricted. The objective of this study is to analyze the coverage of PubMed across specialties and over time. Study Design and Setting: We use the more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…However, even though MEDLINE and Web of Science Core Collection showed a high amount of overlap, the use of both databases was necessary in our scoping review since they provide unique references indexed in either one or the other database. This underlines the importance of using MEDLINE and Web of Science Core Collection in dementia-related evidence synthesis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though MEDLINE and Web of Science Core Collection showed a high amount of overlap, the use of both databases was necessary in our scoping review since they provide unique references indexed in either one or the other database. This underlines the importance of using MEDLINE and Web of Science Core Collection in dementia-related evidence synthesis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are clear guidelines on database use, e.g., for conducting Cochrane reviews [ 32 ]. Specifically, for dementia care research, Frandsen et al [ 33 ] determined the coverage of PubMed according to eligible references in dementia-related Cochrane reviews. The authors concluded that approximately three out of four references might be covered by searching PubMed.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be relevant to treat them as independent databases when conducting academic literature searches. PubMed includes all MEDLINE references as well as up-to-date citations, books and book chapters, and references from journals not indexed in MEDLINE, such as PMC journals [14,29]. The larger quantity of content in PubMed compared to MEDLINE (91% of PubMed content is indexed in MEDLINE [21],) might contribute to more relevant references when conducting a SR. On the other hand, PMC literature has been criticized for potentially reducing the quality of PubMed, due to its informal reevaluation process (prior to 2017), though most manuscripts in PMC are also published in MEDLINE indexed journals [21].…”
Section: Discussionmentioning
confidence: 99%
“…references not found elsewhere within a given field. These questions have been investigated earlier in qualitative research in general terms [7], within the field of depression [8] as well as in quantitative research [9][10][11][12][13][14][15] with one study exploring diabetes mellitus [16]. However, no previous studies have investigated SRs of qualitative research regarding diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Database choice is closely tied to coverage which can be investigated using a number of different approaches: a specific topic or medical specialty as an example, coverage of a selection of journals (width and depth), coverage of different document types, and finally, a gold standard can form the basis for an examination of database coverage. The latter approach is used in a large scale of the included studies in all Cochrane reviews published from 2012 to 2016 (1). By including all Cochrane reviews, we focus on intervention studies.…”
mentioning
confidence: 99%